The platform will undergo maintenance on Sep 14 at about 7:45 AM EST and will be unavailable for approximately 2 hours.
2015
DOI: 10.1021/acs.bioconjchem.5b00369
|View full text |Cite
|
Sign up to set email alerts
|

Fluorescent Bisphosphonate and Carboxyphosphonate Probes: A Versatile Imaging Toolkit for Applications in Bone Biology and Biomedicine

Abstract: A bone imaging toolkit of 21 fluorescent probes with variable spectroscopic properties, bone mineral binding affinities, and antiprenylation activities has been created, including a novel linking strategy. The linking chemistry allows attachment of a diverse selection of dyes fluorescent in the visible to near-infrared range to any of the three clinically important heterocyclic bisphosphonate bone drugs (risedronate, zoledronate, and minodronate or their analogues). The resultant suite of conjugates offers mul… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

1
51
0

Year Published

2016
2016
2020
2020

Publication Types

Select...
7
2

Relationship

0
9

Authors

Journals

citations
Cited by 47 publications
(53 citation statements)
references
References 50 publications
1
51
0
Order By: Relevance
“…Data from previous studies showed that fluorescently labeled bisphosphonates, e.g. Zol-AF647, mainly accumulate in bones, which is similar to their unlabeled parent bisphosphonates (Junankar et al, 2015; Roelofs et al, 2012; Sun et al, 2015). However, conjugating AF647 onto Zol affects its physicochemical properties.…”
Section: Resultsmentioning
confidence: 90%
See 1 more Smart Citation
“…Data from previous studies showed that fluorescently labeled bisphosphonates, e.g. Zol-AF647, mainly accumulate in bones, which is similar to their unlabeled parent bisphosphonates (Junankar et al, 2015; Roelofs et al, 2012; Sun et al, 2015). However, conjugating AF647 onto Zol affects its physicochemical properties.…”
Section: Resultsmentioning
confidence: 90%
“…To readily detect Zol, 2% (w/w) of the Zol was the fluorescently labeled Zol-AF647. It has been reported that free bisphosphonates and their relative fluorescently labeled bisphosphonates, including Zol and Zol-AF647, have very similar in vivo distributions (Junankar et al, 2015; Roelofs et al, 2012; Sun et al, 2015). C57BL/6 mice were i.v.…”
Section: Resultsmentioning
confidence: 99%
“…Inspection of the bone imaging literature indicates increasing community interest in using fluorescent probes for preclinical studies, 4446 and there are also ongoing efforts to produce multimodality probes for clinical imaging. 47,48 Furthermore, researchers are beginning to develop bone-targeting systems for drug delivery and bone tissue engineering.…”
Section: Resultsmentioning
confidence: 99%
“…To determine whether the ZA was internalized by the macrophages, the BMDMs were treated with 10 µM of the fluorescent‐labeled ZA analog 5‐FAM‐ZOL (BV111001; BioVinc, Los Angeles, CA, USA) (30). After treatment for the indicated time, the cells were thrice washed with PBS and fixed for 10 min in 4% paraformaldehyde.…”
Section: Methodsmentioning
confidence: 99%